Characterization of different metal oxide promoted alumina catalyst - S.M. Anisuzzaman; Awang Bono; Duduku Krishnaiah; F. A. Lahinb; C. Ramlan (Universiti Malaysia Sabah, 2017)
In this study, different metal oxide alumina promoted catalysts were prepared and characterized. All the catalysts (CaO/Al2O3, CuO/Al2O3, FeO/Al2O3, MnO/Al2O3, NiO/Al2O3 and ZnO/Al2O3) were prepared using the incipient wetness impregnation method followed by drying and calcination. The characterization of all six samples of catalysts was done to determine the surface morphology, porosity, functional group, thermal stability, metal content and particle size distribution. Scanning electron microscope (SEM) analysis of samples showed that there were pores on the surface of the alumina. Mercury intrusion porosimetry (MIP) showed that copper oxide alumina promoted (CuO/Al2O3) had the high porosity which is 36.77 m2 /g followed by zinc oxide (ZnO/Al2O3), calcium oxide (CaO/Al2O3) nickel oxide (NiO/Al2O3) manganese oxide (MnO/Al2O3) and ferric oxide alumina promoted (FeO/Al2O3) catalysts. Fourier transform infrared spectroscopy (FTIR) analysis showed the presence of by-product existed in all catalysts. Atomic absorption spectroscopy (AAS) analysis showed the presence of Cu, Fe and Zn in the CuO/Al2O3, FeO/Al2O3 and ZnO/Al2O3, while Ca was absent in CaO/Al2O3. Besides, through thermo-gravimetric analyzer (TGA) and differential thermal analysis (DTA), all the catalysts showed a slight decrease in weight which can be considered as a stable catalyst. The particle size distribution analysis using the Zetasizer showed the particle size mean based on the intensity of CaO/Al2O3, CuO/Al2O3, FeO/Al2O3, MnO/Al2O3, NiO/Al2O3 and ZnO/Al2O3 were 2305 nm, 5560 nm, 5560 nm, 1281 nm, 1281 nm and 3580 nm, respectively.